Firsekibart for gouty arthritis: a review of clinical efficacy, safety, and therapeutic positioning - Gao-Yi Yi; Hong-Mei Diao; Qiang Zhou; Xiu-Qiong Liu; Yang-Sen He (The Egyptian Journal of Internal Medicine, 2026)
Abstract Introduction Gout is the most prevalent inflammatory arthritis worldwide, yet conventional treatments—non-steroidal anti-inflammatory drugs, colchicine, and glucocorticoids—are limited by efficacy ceilings, safety concerns, and contraindications in patients with renal impairment or cardiovascular disease. Firsekibart, a novel fully human anti-interleukin-1β monoclonal antibody, was approved in China in 2025 for acute gouty arthritis in patients unsuitable for standard therapies. Aim This narrative review synthesizes the clinical evidence for firsekibart in gouty arthritis, examining its pharmacological properties, efficacy, safety profile, and therapeutic positioning in gout management. Methods Published literature was identified through structured searches of PubMed, Embase, China National Knowledge Infrastructure (CNKI), and ClinicalTrials.gov through June 2026. Included studies encompassed Phase 1 through Phase 3 clinical trials, open-label extension studies, conference abstracts, and peer-reviewed publications. Conclusion Firsekibart provides a single-dose therapeutic paradigm combining rapid analgesia with sustained flare prevention (87–94% risk reduction over 12–24 weeks across active-controlled trials) and generally favourable short- to medium-term safety, with no treatment-related serious adverse events reported in the gout trials. It represents a meaningful addition to the gout therapeutic armamentarium; longer-term, international, and real-world evidence remains needed.